2012
DOI: 10.1128/iai.06075-11
|View full text |Cite
|
Sign up to set email alerts
|

Escherichia coli Uropathogenesis In Vitro : Invasion, Cellular Escape, and Secondary Infection Analyzed in a Human Bladder Cell Infection Model

Abstract: Uropathogenic Escherichia coli (UPEC) strains are capable of invading bladder epithelial cells (BECs) on the bladder luminal surface. Based primarily on studies in mouse models, invasion is proposed to trigger an intracellular uropathogenic cascade involving intracellular bacterial proliferation followed by escape of elongated, filamentous bacteria from colonized BECs. UPEC filaments on the mouse bladder epithelium are able to revert to rod-shaped bacteria, which are believed to invade neighboring cells to ini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
179
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(193 citation statements)
references
References 44 publications
13
179
1
Order By: Relevance
“…It has been suggested that UPEC filamentation is induced by intracellular stimuli from the invaded BEC itself or from recruited polymorphonuclear leukocytes (Horvath et al, 2011;Justice et al, 2006). However, recent results from our group showed that the physical and chemical growth conditions in the urinary tract can lead to strong and reversible filamentation of wild-type UPEC (Andersen et al, 2012). Specifically, we found that surface colonization in flow chambers in continuous flow of highly concentrated human urine leads to strong filamentation similar to what is observed in mouse UTI models (Justice et al, 2004) and urine samples from UTI patients (Rosen et al, 2007).…”
Section: Introductionmentioning
confidence: 85%
See 3 more Smart Citations
“…It has been suggested that UPEC filamentation is induced by intracellular stimuli from the invaded BEC itself or from recruited polymorphonuclear leukocytes (Horvath et al, 2011;Justice et al, 2006). However, recent results from our group showed that the physical and chemical growth conditions in the urinary tract can lead to strong and reversible filamentation of wild-type UPEC (Andersen et al, 2012). Specifically, we found that surface colonization in flow chambers in continuous flow of highly concentrated human urine leads to strong filamentation similar to what is observed in mouse UTI models (Justice et al, 2004) and urine samples from UTI patients (Rosen et al, 2007).…”
Section: Introductionmentioning
confidence: 85%
“…In this cyclic pathway UPEC invades the superficial bladder epithelial cell (BEC) layer, forms intracellular colonies and ultimately breaks out of the host cell in the form of highly filamentous bacteria (reviewed in Justice et al, 2008;Kau et al, 2005). By reverting back to its normal rod-shape through coordinated cell division each UPEC filament can give rise to multiple infectious single bacteria (Andersen et al, 2012;Justice et al, 2004), which can reinvade neighboring cells of the bladder epithelium. The intracellular uropathogenic cascade enables the bacterium to survive the host immune response as well as antibiotic treatment and is believed to account for the frequent recurrences of this type of infection.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The ease of use, low cost, and amenability to high-throughput assays, genetic manipulation, and biochemical analysis make cell culture-based systems attractive alternatives to many animal infection models. Recent advances with flow cell technology even make it possible to examine UPEC-host interactions using bladder cell monolayers in the presence of urine flow, mimicking conditions within the urinary tract during an actual UTI (181). Despite the proven utility of cell culture-based model systems, they cannot fully recapitulate the complexity of the host environment with its myriad cell types, complicated tissue architecture, variable nutrient levels, and teeming host defenses.…”
Section: Cell Culturementioning
confidence: 99%